The effect of melting land-based ice masses on sea level around Australian coastline - Fleming, Kevin; Tregoning, P.; Kuhn, Michael; Purcell, A.; McQueen, H. (Taylor & Francis Co Ltd, 2012)
Changes in relative sea-level (RSL) are generally caused by variations in sea surface heights from steric effects (thermal expansion and salinity changes) and the mechanical response of the Earth to past and current redistributions of ice and water between land and oceans. This paper focuses on the latter, where we present scenario calculations of the spatial variability in present-day RSL change around the Australian coastline resulting from melting land-based ice masses. Three scenarios are investigated: (1) the ongoing effect of glacial isostatic adjustment (GIA) arising from ice- and water-load redistribution during the last glacial–interglacial transition; (2) the effect of present-day changes in the Greenland and West and East Antarctic ice sheets (GIS, WAIS and EAIS, respectively) and two regions of major mountain glaciation, Alaska and Patagonia; and (3) a hypothetical complete melting of the GIS, WAIS and EAIS occurring over 5000 years. The first scenario shows falling RSL around Australia of the order of 0.4 to 1.2 times the average value around the coast (equivalent to a RSL fall of between 0.2 and 0.6 mm/a). For the second scenario, the spatial variability is strongly dependent upon the location of each ice mass relative to Australia. For Greenland and Patagonia, the resulting changes to the Earth’s rotation strongly affect the spatial variability, while the direct gravitational effect is more important when considering the Antarctic ice sheets.The variability associated with the first two scenarios becomes clearer when examining RSL change estimates for the locations of tide-gauge stations around the Australian coast, especially for the ongoing GIA (a south-to-north increase in the simulated rate of RSL change), the WAIS (east-to-west increase) and the EAIS (south-to-north increase), with the melting of the EAIS potentially having the greatest influence on the variability of the melting land-based ice contribution to RSL change around Australia. The spatial variability associated with the third scenario is strongly influenced over century-length time-scales by the resulting changes in the Earth’s rotation and the direct gravitational attraction of the ice masses, while after several thousand years the uplift of the continent by mantle material displaced towards it by increased ocean loading becomesmore prominent. It must, however, be kept in mind that the spatial variability associated with thesescenarios is generally a small proportion of the total RSL change, and that the steric (especially thermosteric) contribution is not included in these results.